The 'Top 10' Challenges for Health Technology Assessment: INAHTA Viewpoint. (28th November 2020) - O'Rourke, Brian; Werkö, Sophie Söderholm; Merlin, Tracy; Huang, Li Ying; Schuller, Tara
Abstract : The International Network of Agencies for Health Technology Assessment (INAHTA) spans the globe as a network of 50 publicly-funded health technology assessment (HTA) agencies supporting health system decision making for 1.4 billion people in thirty countries. Agency members are non-profit HTA organizations that are part of, or directly support, regional or national governments. Recently, INAHTA surveyed its members to gather perspectives from agency leadership on the most important issues in HTA today. This paper describes the top 10 challenges identified by INAHTA members. Addressing these challenges requires a call for action from INAHTA member agencies and the many other actors involved in the HTA ecosystem. In opening this call for action, INAHTA will lead the way; however, a comprehensive undertaking from all players is needed to effectively address these challenges and to continue to evolve HTA in its role as a strong and effective contributor to health systems.